Chitosan and anisodamine improve the immune efficacy of inactivated infectious spleen and kidney necrosis virus vaccine in Siniperca chuatsi. Issue 89 (June 2019) - Zhang, Jiacheng; Fu, Xiaozhe; Zhang, Yanqi; Zhu, Wentao; Zhou, Yong; Yuan, Gailing; Liu, Xiaoling; Ai, Taoshan; Zeng, Lingbing; Su, Jianguo
Abstract: Siniperca chuatsi is an economically important fish in China, but infectious spleen and kidney necrosis virus (ISKNV) causes high mortality and significant economic losses. Currently, vaccination is the most promising strategy to prevent infectious diseases, while adjuvant can effectively enhance immune responses. In this study, inactivated ISKNV vaccine was prepared, then poly (I:C), chitosan, anisodamine and ims1312 were used as adjuvants to evaluate the effect on the immune responses and ISKNV replication. Chitosan could strongly boost the protection of liver and spleen tissues by pathological sections. In serum, poly (I:C) and chitosan group had protective effect on catalase, acid phosphatase, blood urea nitrogen. mRNA expressions showed these adjuvants induced the cytokines of early immune responses ( TNF-α, Viperin ) in both spleen and mesonephron by real time quantitative RT-PCR assays. Meanwhile, poly (I:C), chitosan and anisodamine were significantly improved the antiviral function and inhibited ISKNV replication. Chitosan and anisodamine played a significantly protective role in the immune protective rate test. The results indicated that all the four adjuvants are valid in the inactivated ISKNV vaccine, and chitosan is recommended preferentially. The present study provides reference for other animal vaccine adjuvants. Highlights: Chitosan and anisodamine as adjuvant enhance the survival rate. Chitosan and poly (I:C) strongly improve the effects of the whole immune levels. Chitosan and anisodamine strengthen the vaccine inhibiting ISKNV replication.